Effect of Cholecalciferol Supplementation on Disease Activity and Quality of Life of Systemic Lupus Erythematosus Patients: A Randomized Clinical Trial Study - Fiblia Fiblia; Iris Rengganis; Dyah Purnamasari; Alvina Widhani; Teguh H Karjadi; Hamzah Shatri; Rudi Putranto (Interna Publishing, 2022)
Background: Increase in the prevalence and survival rates has led to the assessment of disease activity and quality of life of SLE patients as targets in treatment. Cholecalciferol was considered as having a role in reducing disease activity and improving quality of life. Methods: A double blind, randomized, controlled trial was conducted on female  outpatients aged 18-60 years with SLE, consecutively recruited from September to December 2021 at Cipto Mangunkusumo Hospital. Sixty subjects who met the research criteria were randomized and equally assigned into the cholecalciferol and placebo groups. The study outcomes were measured at baseline and after 12 weeks of intervention. Results: Out of 60 subjects, 27 subjects in cholecalciferol group and 25 subjects in placebo group completed the intervention. There was a significant improvement on the level of vitamin D (ng/ml) after intervention in the cholecalciferol group, from an average of 15,69 ng/ml (8.1-28.2) to 49,90 ng/ml (26-72.1), and for the placebo group from 15,0 ng/ml (8.1-25,0) to 17.35 ng/ml (8.1-48.3) (p<0,000). Results of the MEX-SLEDAI score showed significant differences in both groups after the intervention, with a significant decrease in the cholecalciferol group from 2,67 (0-11) to 1,37 (0-6), compared to the placebo group from 2,6 (0-6) to  2,48 (0-6) (p<0,001). There were no significant differences on the quality of life in both groups. Conclusion: Supplementation of cholecalciferol 5000 IU/day for 12 weeks was statistically significant in increasing vitamin D levels and improving disease activity, but did not significantly improve the quality of life of SLE patients.